Teacher’s Professionality in Teaching Social Sciences - Azahra, Hafizza; Susanti, Eka (Graduate Program Magister Manajemen Pendidikan, 2025)
This research examines the professionalism of teachers in teaching social studies at the SMP Cerdas Murni. The aim is to describe how professional teachers teach social studies at this school. Using a qualitative approach, the research applies an analytical descriptive method with data collection through observation, interviews, and documentation. The findings show that social studies teachers at the SMP Cerdas Murni demonstrate strong mastery of the four key competencies: pedagogical, personality, social, and professional. These competencies are critical in creating an effective learning atmosphere, sparking student interest in learning, developing their potential, and motivating achievement, thereby significantly contributing to the success of the learning process. The professionalism of these teachers is influenced by input factors, such as educational background and teaching experience, and output factors, including facilities and a supportive work environment. The principal actively enhances teacher professionalism through several strategies: involving teachers in professional development activities, holding regular performance evaluations, encouraging innovative teaching practices, and providing both formal and emotional support. These efforts aim to continuously improve teaching quality, positively impact student achievement, and raise overall educational standards.